L’interdisciplinarité en pratique dans les sciences de l’environnement : des enjeux épistémologiques aux défis de la publication scientifique - Gabrielle Bouleau; Rémy Petitimbert; Thibault Boughedada (Développement Durable et Territoires)
This interview with Gabrielle Bouleau is part of a series of exchanges conducted as part of the anniversary issue of the journal Développement durable & territoires. by drawing up her scientific trajectory and the epistemological challenges of her major contributions to DD&T, Gabrielle Bouleau underlines the pivotal role that the journal has played in structuring a research path which is anchored in interdisciplinarity and in constant iteration with the territories. The interview thus offers a panoramic view of the expectations – in particular the capacity to address emerging issues – with regards to DD&T, which 20 years after its creation, is now well established in the field of French-speaking journals on environmental social sciences applied to territory.